Julgamento antecipado em segundo grau: a utilização do § 3º do art. 515 do CPC nos julgamentos de agravo de instrumento - Borges, Flávio Buonaduce (2008)
This parar begins with a historic approach to the recourses, going through a point by analysis of the origin as well as the existing effects on the appeal and on the bill of review, arriving at its core by examining the possibility of using an ability attributed to the courts, through the appraisal of an appeal, in the judgement of a bill of review. Such a possibility is found regulated in § 39, of article 515 of the Civil Process Code, where it is foreseen that in cases of the Gonclusionof lhe process wíthout judgement of the merit, the court may, upon finding itself convinced about the matter placed betore it, and being only of law, immediately decide the dispute. Therefore, the court wíll evaluate the possíbility of the application of the rule of §3º, article 515, of the Civil Process Code in the judgament of the BiII of Revíew, deciding upon the merit of the controversy, even if there has not been a decísion by the first instance court